Safety and Belonging in Immigrant-Serving Districts: Domains of Educator Practice in a Charged Political Landscape - Rebecca Lowenhaupt; Dafney Blanca Dabach; Ariana Mangual Figueroa (SAGE Publishing, 2021)
Drawing from a context of reception framework, this article asks the following questions: How do educators describe issues of safety and belonging in the context of a charged immigration policy climate? What practices have educators developed to support immigrant-origin youth? And, what are the relationships between educators' perceptions of safety and belonging and educator practices? We analyze educators' survey responses administered across six school districts in different contexts across the United States, including the Northeast, Midwest, South, and West. We synthesize four domains of educator practice: signaling affirmation, building shared knowledge and capacity, finding and mobilizing resources, and creating space for conversation. Through this work, we connect the domain of safety as a perennial theme to safety as a practice. We discuss the implications of this and the need for future work that critically analyzes educators' practice in relation to immigrant-origin youth for more generative contexts-contexts of development, not merely reception.